“Producción de Frejol canario de mata (Phaseolus vulgaris) con tres diferentes dosis de fertilizantes orgánicos en el Recinto Pilancón” - Llomitoa Gavilanez, Angel Alberto (2020)
In order to evaluate the production of bush canary beans, it was carried out on the farm “Angamarca la Vieja” geographical coordinates 01° 06´ S 95” S latitude; S and y 79° 0´ S 10” W at an altitude of 1700m belonging to the Ramon Campaña Parish, Pangua Canton, Cotopaxi Province, the objective was to evaluate the production of bush canary beans (Phaseolus vulgaris) in the village Pilancon to the application of three different doses of organic fertilizers, two fertilizers were applied (chicken manure and worm humus), with a duration of 90 days, the data was taken at 20, 40, 60 and 80 days. The variables evaluated were: number of pods by plant (cm), number of pods, the weight of 100 seeds (g) and production (kg), block design was used completely random (DBCA), with six treatments and four repetitions, plus three controls (two farmer technologies and one absolute control) and 24 plants as an experimental unit. The results show that the fertilization applied with chicken manure in doses of 4gk m2, 6kg m2 and 8kg m2 allowed obtaining better results, while the other treatments obtained lower results in the variables: plant height, number of pods, the weight of 100 seeds, and production. The highest benefit/cost ratio was obtained in the control with $ 1.00 followed by farmer 2 chicken manure technology with $ 0.94.